A transposon insertion in FLOWERING LOCUS T is associated with delayed flowering in Brassica rapa. (December 2015) - Zhang, Xueming; Meng, Lin; Liu, Bo; Hu, Yunyan; Cheng, Feng; Liang, Jianli; Aarts, Mark G.M.; Wang, Xiaowu; Wu, Jian
Highlights: Two major QTLs for flowering time were detected twice in different growing seasons. An ortholog of AtFT, named as BrFT2, and BrFLC2 were candidate genes for the QTLs. A naturally occurring transposon insertion in BrFT2 were identified. Mutated BrFT2 allele resulted in late flowering in both long-day and short-day conditions. Abstract: Long days and vernalization accelerate the transition from vegetative growth to reproductive growth in Brassica rapa . Bolting before plants reach the harvesting stage is a serious problem in B. rapa vegetable crop cultivation. The genetic dissection of flowering time is important for breeding of premature bolting-resistant B. rapa crops. Using a recombinant inbred line (RIL) population, we twice detected two major quantitative trait loci (QTLs) for flowering time in two different growing seasons that were located on chromosomes A02 and A07, respectively. We hypothesized that an orthologue of the Arabidopsis thaliana FLOWERING LOCUS T ( FT ) gene, named as BrFT2, was the candidate gene underlying the QTL localized to A07. A transposon insertion in the second intron of BrFT2 was detected in one of the parental lines, which was predicted to generate a loss-of-function allele. Transcription analysis revealed that the BrFT2 transcript was not present in the parental line that harbored the mutated allele. RILs carrying only the mutated BrFT2 allele showed delayed flowering regardless of growing seasons when compared to RILs carrying the wild-type BrFT2 allele. These data suggest that BrFT2 is involved in flowering time regulation in controlling flowering time in B. rapa .